A meta‐analysis of case‐control studies examining sporadic campylobacteriosis in Australia and New Zealand from 1990 to 2016. (24th June 2020) - Varrone, Liana; Glass, Kathryn; Stafford, Russell J.; Kirk, Martyn D.; Selvey, Linda; ,
Abstract: Objective : We conducted a meta‐analysis of case‐control studies to identify locally relevant risk factors for sporadic campylobacteriosis in Australia and New Zealand. Methods : We searched Medline, Web of Science, ProQuest and Google Scholar using PRISMA guidelines. Reference lists and grey literature were hand‐searched. Meta‐analyses were conducted in the R package 'metafor' using published odds ratios and 95% confidence intervals. Results : We identified 325 articles, from which we included 10 that described case‐control studies. Four risk factors were statistically significant in the meta‐analysis: eating undercooked poultry (OR=4.28, 95%CI 3.09–5.93); eating poultry cooked outside the home (OR=2.13, 95%CI 1.66–2.72); having pet chickens (OR=3.29, 95%CI 2.12–5.10); and overseas travel (OR=5.55, 95%CI 3.20–9.63). Among children, having pet dogs showed elevated but not significant risk (OR=1.57, 95%CI 0.99–2.49). Conclusions : We identified consumption of chicken meat and contact with domestic chickens as important risk factors for campylobacteriosis in Australia and New Zealand. Implications for public health : While consumption of chicken meat is a well‐known risk factor for campylobacteriosis, zoonotic transmission is often overlooked. This research indicates a greater need for public health awareness surrounding zoonotic campylobacteriosis, especially for young children.